Other: Ambiguity, Constraints, and Change - Amaral, Patrícia (Language and Linguistics E-Books Online, Collection 2025., 2026)
This book is the first to explore the properties of words across languages that correspond to English other . When can Italian altro mean 'different' or 'additional'? And why do these meanings often lexicalize together? How can we explain that cross-linguistically, such words may also mean 'second' or 'remainder'? This book brings together data from multiple language families including Eskaleut, Finno-Ugric, Germanic, and Romance, to address these questions. It presents analytic, typological, corpus-based, and computational approaches to investigate linguistic constraints and pragmatic factors that play a role in disambiguation, as well as historical developments that such words undergo.